Microstructural stability of TMS-238TM Ni-base superalloy during long-term exposure at high temperature. Issue 10 (3rd July 2021) - Sowa, Roman; Goehler, Thomas; Dankl, Lisa; Kirzinger, Anna; Budziak, Andrzej; Parlinska-Wojtan, Magdalena
Abstract : The microstructure evolution in Re–Ru containing high generation Ni-base single crystal superalloy has been investigated during long-term isothermal exposure at 1000°C. The chemical and physical characteristics are determined by means of differential scanning calorimetry (DSC), X-ray diffraction (XRD), scanning electron microscopy (SEM) and Transmission electron microscopy (TEM) measurements. In addition to the initial γ/γ' phase structure, formation of HCP-structured Re–Ru–Ni-rich phase is confirmed. Based on high-resolution TEM imaging and phase structure analysis the theoretical atomistic model presenting the interfaces between the phases was constructed and evaluated with respect to precipitation kinetics. Growth of plate-like precipitates occurs mainly through the plate edge area due to stacking fault sequences between the surrounding matrix and the precipitates, while thickening is very limited due to good coherency with the surrounding phase in the longitudinal direction.